A Review Article of Gastroretentive Drug Delivery System - R. Margret Chandira (Journal of Global Pharma Technology, 2020)
The purpose of writing this review was to investigate, compile and present the recent as well as past literatures in more concise way with special focus on approaches which are currently utilized in the prolongation of gastric residence time. Drug absorption in GIT varies and increased gastric retention time of the dosage form extends the time of drug absorption. Thereby implementing site specific drug release in the stomach for local and systemic effect. It is very useful for the drugs which having narrow absorption Rate. These includes floating system, swelling and expanding system, bio / mucoadhesive system, high density system and other delayed gastric emptying devices.